2022
DOI: 10.1128/spectrum.00893-21
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Diet-Microbiota-Metabolism Interactions in Overweight and Obese Pregnant Women: a Metagenomics Approach

Abstract: We observed partially distinct diet-gut microbiota-metabolism and inflammation responses in overweight and obese pregnant women. In overweight women, gut microbiota community composition and the relative abundance of A. finegoldii were associated with an inflammatory status. In obese women, a higher dietary quality was related to a higher gut microbiota diversity and a healthy inflammatory status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
3
2
0
Order By: Relevance
“…In our study, the overall gut microbiota diversity did not differ in individuals consuming higher inflammatory diets. While distinct patterns of beta diversity composition in pregnant individuals with better diet quality have been previously reported (61, 62), recent microbiome-pregnancy cohorts have not identified alterations in beta diversity by diet quality (63,64), supporting our study observations. At the taxonomic level, several ASVs varied with dietary inflammatory potential.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the overall gut microbiota diversity did not differ in individuals consuming higher inflammatory diets. While distinct patterns of beta diversity composition in pregnant individuals with better diet quality have been previously reported (61, 62), recent microbiome-pregnancy cohorts have not identified alterations in beta diversity by diet quality (63,64), supporting our study observations. At the taxonomic level, several ASVs varied with dietary inflammatory potential.…”
Section: Discussionsupporting
confidence: 90%
“…All DII scores were within the normal limits specified by the DII score authors [29]. While distinct patterns of beta diversity composition in pregnant individuals with better diet quality have been previously reported [61,62], recent microbiome-pregnancy cohorts have not identified alterations in beta diversity based on diet quality [63,64], supporting our study observations. At the taxonomic level, several ASVs varied with dietary inflammatory potential.…”
Section: Discussionsupporting
confidence: 88%
“…All DII scores were within the normal limits specified by the DII score authors [29]. While distinct patterns of beta diversity composition in pregnant individuals with better diet quality have been previously reported [61,62], recent…”
Section: Discussionsupporting
confidence: 59%
“…In non‐pregnant populations, the healthy eating index (adherence to the US dietary guidelines) and the MDS have been correlated with microbiota diversity and composition 63 . In a previous study, diet quality in women with obesity, but not women classified as overweight, was found to be associated with diversity and gut microbiota composition in early pregnancy (<18 weeks) 64 . Ruebel et al reported positive associations between dietary components and genus‐level abundances when dietary intakes and genus level abundances were averaged over the course of pregnancy 65 .…”
Section: Discussionmentioning
confidence: 99%
“…63 In a previous study, diet quality in women with obesity, but not women classified as overweight, was found to be associated with diversity and gut microbiota composition in early pregnancy (<18 weeks). 64 Ruebel et al reported positive associations between dietary components and genus-level abundances when dietary intakes and genus level abundances were averaged over the course of pregnancy. 65 There are limited data on the effect of dietary intake on the human microbiota in the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%